GAMIFIED SYSTEMS DEVELOPMENT FOCUSED ON EDUTERTAINMENT AND PLAYER: AN ANALYSIS OF BARTLE AND MARCZEWSKI ARCHETIPES - Christianini, Shelley Navari [UNESP]; De Grande, Fernando Chade [UNESP]; Americo, Marcos [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This paper presents a development methodology about gamification systems, in which discuss the learning in these media from entertainment, concept defined as Edutertainment. By employing gamification in this type of production, it is believed that the investigation must be focused only on the playing techniques. However, from a literature review, it was found that the focus should be on the player, considering their feelings and real motivations to stay in the system. As a result, it is providing a comparative overview on the theories of Bartle (1996, 2005) and Marczewski (2015) with the main differences between player types in gaming environments and gamification systems, especially with regard to motivational strategies in the context of education.
Keywords: Gamification; Edutertainment; Gamification system; Players; Motivation